PUSAT SENI KONTEMPORER DI BANJARBARU - Kenny Chris Imantaka Dau; J.C Heldiansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Contemporary Art Center in Banjarbaru is a place that presents a place to facilitate artists and the general public who are interested in various elements of art that are developing now, such as installation art. This center of contemporary art aims to create an environment that can indicate the behavior of artists and contemporary art, so that it can be used as an art space for artists and the general public to collaborate with each other in various branches of art. By using combined metaphor method and character concept, it is expected to be able to create an art center design with contemporary theme projection that can represent the identity of various art to collaborate, taking into account the elements of contemporary art that are in it and translated into visual architecture.